Malaysia-China Network Trade: A Note on Product Upgrading - Evelyn Devadason (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
The paper addresses the importance of network trade between Malaysia and China and assesses the extent of product upgrading in components traded. The study brings to the fore the following. First, China is emerging as an important market for component imports relative to component exports. As such the increase in two-way flows of parts and components for further processing and development, implying a shift away from assembly-end operations, remains insignificant. Second, network trade appears to have improved the quality of exports (reflecting the 'moving up of the value chain') destined to China, but the gaps between the unit values of export and imports have narrowed in the recent past, implying less product development. network trade, two-way trade, unit values, relative unit values, product upgrading
hdl:10398/7403
Keywords: 330